MyChildBus: Real-Time School Bus Monitoring and Rides Tracking Mobile Application for Parents - ZULKARIA, FATIN NABILAH; DARMAN, ROZANAWATI (Applied Information Technology And Computer Science, 2025)
The absence of real-time school bus tracking systems in Malaysia raises significant concerns among parents and school bus operators regarding student safety and operational inefficiencies. This project aims to address these issues by developing “MyChildBus”, a mobile application that enables parents to track their children’s school bus location in real-time. The proposed application is designed for parents, school bus drivers, and administrator from a school bus company as users, with modules such as registration and login, communication, live location tracking, route navigation, incident reporting and handling, student, driver and bus management, and reporting. Using the Prototyping Model, the app integrates Firebase for real-time database management, and Google Maps API for live location tracking. The results of functional testing and User Acceptance Testing (UAT) have proven the achievement of this app of becoming a user-friendly location tracking application fulfilling both of its functional and non-functional requirements. Hence, future work could be done is to expand this application capabilities to support multiple bus operators rather than being used by a single bus company only at a time.